Photo-oxidative degradation of motorcycle helmets in Hanoi, Vietnam: A prospective preliminary study. (12th September 2016) - Ramli, Roszalina; Che Man, Zuraidah; Nordin, Rifqah; Abdul Karim, Fadzlina; Rashdi, Muhd Fazlynizam; Oxley, Jennie; Viet Cuong, Pham
ABSTRACT: Objective: Vietnamese spend hours travelling on the road using their motorcycles. Their helmets are exposed continuously to sunlight and rain. The objectives of this study were to determine the association between the effect of photo-oxidative degradation (POD) of the outer shells and helmet age on helmet damage. The micro-structural change of the outer shell was also investigated. Methods: This was a prospective, cross sectional study recruiting injured motorcyclists from Hanoi, Vietnam hospital. The participants were interviewed by a trained researcher. The participants' helmets were collected post-crash. Initially, the helmets were examined for their type and external characteristics. A 3 cm × 3 cm cut was made on the helmet in the impacted and non-impacted areas (control). These areas were investigated for evidence of POD and presence of micro-cracks and material disintegration. 50 participants were enrolled. Sources of information included questionnaire and laboratory analyses. The helmet factors of interest were age of the helmet, exposure of helmet to sunlight and rain (duration/day) and history of previous impact. Laboratory analyses included Fourier Transform Infra Red (FTIR) for degradation and scanning electron microscopy (SEM) for micro-structural examination. Results: Majority of the helmets was the open-face type, 40 (80.0%). 31 (62.0%) helmets aged less than three years (LTY) and 19 (38.0%) were three years old or more (MTY). 19 (61.3%) of the LTY helmets and 12 (63.2%) MTY helmets showed evidence of POD. The duration of helmet exposure to sunlight was between 93 to 6570 hours (mean 2347.74 hours; SD 1733.39). The SEM showed 15 helmets (30%) with micro-fractures, 21 helmets (42.0%) with material disintegration. Prolonged uv exposure to the ABS helmets resulted in changes in the helmet material in the form of material disintegration and microcracks and this association was statistically significant (p = 0.03). Conclusion: POD occurs due to routine exposure to the ultraviolet light. Prolonged uv exposure affects outer shell surface material integrity.